Pengaruh Frekuensi Penyiraman Terhadap Total Luas Daun Pada Beberapa Jenis Bibit Unggul Kelapa Sawit (Elaeis guinensis Jacq.) Yang Bermesokarp Tebal Di Main Nursery Umur 4 Sampai 7 Bulan - Roy Marulitua Tampubolon; Irsal Irsal; Charloq Charloq (Jurnal Agroekoteknologi, 2019)
Watering is a method that used to fulfill the water needs of oil palm seedlings in the nursery. In watering that must be considered is the quality and amount of water given and the right watering time. The aim of this research was conducted the Influence of frequency of watering to several types of seeds of high oil palm (Elaeis quineensis Jacq.) that thick mesocarp in the Main Nursery 4 until 7 month. The research was conducted at the Faculty of Agriculture, Universitas Sumatera Utara, Medan (± 32 meters above sea level), which began from September to November 2017. This Research was conducted by using a Factorial Randomized Complete Design with two factors. The first factor is watering consists of in the morning (1 time) and in the morning & evening (2 times), the  second  factor is varieties of oil palm that thick mesocarp consists of Avros, Simalungun and PPKS 540. The observation parameters is the total leaf area. The results showed that frequency treatment of watering is not significant but the varieties of oil palm that thick mesocarp significanly different Avros to Simalungun and PPKS 540 and interaction both had no significant effect on the growth of oil palm seedlings.